Exponential attractor for the Cahn-Hilliard-Oono equation in R^N - Cholewa, Jan W.; Czaja, Radosław (Topological Methods in Nonlinear Analysis, 2023)
We consider the Cahn-Hilliard-Oono equation in the whole of R^N, N≤ 3. We prove the existence of an exponential attractor in H^1(R^N), which contains a global attractor. We also estimate from above fractal dimension of the attractors.